ANALYSIS OF THE IMPLEMENTATION OF CRIMINAL SANCTIONS ON ACTION OF RUBBER CONTINUOUS CRIMINAL ACTION IN RUBBER PLANTATION PT. PERKEBUNAN NUSANTARA VII UNIT KEDATON DESA SABAH BALAU KECAMATAN TANJUNG BINTANG REGENCY OF LAMPUNG SELATAN - Sunia, Muhammad Rizki Mauludin; Ainita , Okta (Progressive Law Review, 2020)
Criminal acts can encourage other people to commit crimes, because many parties involved in criminal acts such as receiving, buying or accommodating goods from the crime of theft. The problem in research is what is the factor that causes the perpetrators to commit criminal acts of rubber gum extraction at PT. Perkebunan Nusantara VII Unit Kedaton, Sabah Balau village, Tanjung Bintang Subdistrict, South Lampung Regency, how to apply criminal sanctions against perpetrators of criminal acts of rubber latex in PT. Perkebunan Nusantara VII Unit Kedaton, Sabah Balau village, Tanjung Bintang Subdistrict, South Lampung Regency, based on Decision Number 313 / Pid.B / 2018 / Pn.Kla and How is the crime prevention effort for perpetrators of criminal acts of rubber latex in PT. Perkebunan Nusantara VII Unit Kedaton, Sabah Balau village, Tanjung Bintang District, South Lampung Regency. The judge should give criminal sanctions to the defendant to consider juridical factors as stipulated in the law. It is expected that the related law Enforcement officers will be more professional in carrying out their duties in upholding the law against perpetrators of fraud in office, and the public has legal awareness to report immediately if there is a similar crime.